THE CONCEPT OF INFORMATION SOURCE AND ITS PLACE IN THE DEVELOPMENT OF JOURNALISM - Mirsultanova Khamida Alisher kizi (Zeta Repository, 2023)
This scholarly article explores the historical foundations of sources on the importance of the source of information in journalism. Although the inscriptions on stones and objects were the first elements of communication, the period in which the first newspapers appeared was the basis for this. In particular, there is scientific evidence from Annus Christi, which is supposed to be the first print publication, about the media that have served as a source of information for the media. There was also talk in the world media about what it looked like to refer to sources for each period. Information, information sources, print media, newspaper, journalist, information, appeal, official source, France.